PRINCIPAL LEADERSHIP, E-LEARNING SUPERVISION, TEACHER PERFORMANCE WITHIN LEARNING TRANSFORMATION AT MADRASAH ALIYAH NEGERI IN JAMBI PROVINCE - Samsu Samsu (INNOVATIO: Journal for Religious Innovations Studies, 2022)
Learning transformation is heavily influenced by leadership, supervision, and teacher performance. Leadership has a very important role in realizing learning transformation, while supervision is a coaching activity on how to assist teachers in improving teaching using e-learning, whereas teacher performance is how to see the result of the work achieved by teachers in realizing learning transformation.This study aims to reveal the relationship between principals' leadership, e-learning supervision, and teacher performance with the transformation of learning at Madrasah Aliyah Negeri (well-known MAN) in Jambi Province. The research approach is a quantitative with a survey method. The research population is civil servant teachers with a total sample of 94 teachers selected by total sampling. The research data were analyzed using Pearson's Product Moment correlation and multiple regression using the SPSS version 23.0. The results showed that the implementation of principal's leadership had a strong significant correlation with learning transformation (77.2%), e-learning supervision had a moderately significant correlation with learning transformation (53.1%), teacher performance had a strong significant correlation with learning transformation (69,7%), and the implementation of principal leadership, e-learning supervision, teacher performance together have a very strong significant correlation with learning transformation (83.5%). This study recommends that learning transformation will increase if the application of principal leadership, e-learning supervision, and teacher performance is given at MAN in Jambi Province. Abstrak: Penelitian ini bertujuan untuk mengungkap hubungan kepemimpinan kepala sekolah, supervisi e-learning, dan kinerja guru dengan transformasi pembelajaran di Madrasah Aliyah Negeri di Provinsi Jambi. Pendekatan penelitian adalah pendekatan kuantitatif dengan metode survei. Populasi penelitian adalah guru Pegawai Negeri Sipil dengan jumlah sampel 94 guru yang dipilih secara total sampling. Data penelitian dianalisis dengan teknik korelasi Product Moment Pearson dan regresi berganda dengan menggunakan aplikasi SPSS versi 23.0. Hasil penelitian menunjukkan implementasi kepemimpinan kepala sekolah berkorelasi signifikan yang kuat dengan transformasi pembelajaran (77,2%), supervisi e-learning berkorelasi signifikan yang sedang dengan transformasi pembelajaran (53,1%), kinerja guru berkorelasi signifikan yang kuat dengan transformasi pembelajaran (69,7%), dan implementasi kepemimpinan kepala sekolah, supervisi e-learning, kinerja guru secara bersama-sama berkorelasi signifikan yang sangat kuat dengan transformasi pembelajaran (83,5%). Penelitian ini merekomendasikan bahwa transformasi pembelajaran akan meningkat jika penerapan kepemimpinan kepala sekolah, supervisi e-learning, dan kinerja guru diberikan di MAN Provinsi Jambi. Kata-kata kunci: kepemimpinan, supervisi e-learning, kinerja guru, transformasi pembelajaran